(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The aim of this paper is to define the concept of compatible maps for n-tupled maps, a new notion propounded by M.Imdad et.al.[13] and prove n-tupled coincidence and n-tupled fixed point theorems in partially ordered metric spaces. Our results generalize, extend and improve the results of [3,7,8,12,13,19.25,26].